Kettő rábaközi település adózási rendszerének összehasonlítása - Horváthné Balázs Edit (2016)
In my essay I have demonstrated the system of the local taxes applied by the self-governments in two Rábaköz settlements, the villages of Rábapordány and Szil. The local self-governments manage according to the budget accepted in the self-government decree. The statutory compulsory and the voluntarily undertaken tasks not endangered dur-ing the performance of its compulsory task are financed on the basis of its budget. The major part of the incomes of self-governments consists of local taxes, assigned central taxes and budget subventions, for this reason I have considered important to investigate the development of these incomes. The decree no. 100 of the year 1990 about local taxes provides clearance for the economic independence and self-determination of the self-governments constituting a separate sub-system within the state budget. In my essay I have reviewed the characteris-tics of local taxes. In my essay after the introduction of the villages of Rábapordány and Szil I have demonstrated the types and extent of the local taxes applied by the individual self-governments. I have compared how the local tax incomes have changed in the investigated period between 2011 and 2015 at the individual self-governments. Every village has intro-duced the poll tax of private persons and the local trade tax. An increase of the tax extent was carried out in any of the villages during the investigated period. None of the self-governments applies the highest tax extent, so there is still possibility to increase local tax incomes. The self-government of Rábapordány has used the possibility of the introduction of building tax as well. The decree no. 189 about local self-governments has fundamentally reconstructed self-governmental economy. The normative financing of self-governments was replaced by task financing. Due to this amendment I have considered necessary to investigate, how the assigned central taxes and budget subventions have developed in the villages of Rábapordány and Szil. During my analyses I have stated that every village has the highest local tax income in 2013. The village of Szil has a higher local tax income in the investigated period than Rábapordány. I have investigated also the local tax income per capita, as the result of which I have stated, that the local tax income per capita is higher in Szil, although building tax was not introduced. The total operation income has reduced from 2013 in both villages due to the reduction of the assigned central tax incomes. During my analysis I have stated that the village of Szil shall manage more income, the tax income per capita is also higher. The Self-Government of Rábapordány did not have to raise a loan for the performance of its operational tasks, however it shall be reconsidered to increase the extent of the trade tax and the poll tax of private persons in order to increase its own incomes.